Interpretasi Waktu Pelaksanaan Ketika Terjadi Perubahan Keadaan: Studi Kasus Penyesuaian Harga dalam Kontrak Pembangunan Saluran Udara Tegangan Ekstra Tinggi Lampung - Wisnuaji, Haryo; Sami’an, S.; Hardjomuljadi, Sarwono (SIGn Jurnal Hukum, 2024)
This normative legal research analyzes disparities in interpreting work execution timelines in implementing the price adjustment clause in the Lampung EHV Overhead Line Construction Contract, which were complicated by significant changes in circumstances. The change in the transmission line route caused delays, triggering differences in viewpoints between PLN and the contractor regarding the cut-off for price adjustment calculations. The contractor argues for using factual indicators of work completion, referring to the doctrine of rebus sic stantibus. Meanwhile, PLN adheres to indicators related to the initial commitment based on the principles of pacta sunt servanda and nemo auditur. This research uses statute, conceptual, and case approaches to examine the Lampung EHV Overhead Line Construction Contract. The research findings show that neither approach, if applied rigidly, produces a fair cut-off. Therefore, this research formulates normative parameters that link the cut-off to the most relevant indicator, plus an adjusted duration that considers the impact of changes in circumstances and internal contractor factors. These parameters aim to achieve contractual justice, legal certainty, and objective, transparent, and accountable implementation of price adjustment based on the principle of good faith.